Strategi Pengembangan Banjar Samu, Singapadu Kaler Sebagai Desa Wisata Di Kecamatan Sukawati, Kabupaten Gianyar - Suarditya, I Made; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA, 2018)
The research aim is to determine development strategy of Banjar Samu as a tourism village. This research used qualitative and quantitative data with source from primary and secondary data. Observation, interview and documentation are data collection techniques. The sample method used purposive sampling while data analysis used descriptive qualitative and SWOT analysis.  Based on the results, the research indicate is that Banjar Samu have tourism potential which is consisted of natural potentials include panorama of rice fields and water springs. While the potential of culture include: community activities, hospitality and attitude of mutual cooperation, temples: building architecture and religious activity, sacred art of barong landung and another arts entertainment such as joged bumbung, arja, gambelan geguntangan, as well as local craft communities such as wood carving, silver handicrafts, yoga-meditation activity and sekaa such as sekaa gong,  joged, geguntangan, arja, angklung, subak and sekaa santi. Based on the analysis of SWOT Matrix, the results obtained by SO strategies are improving the quality of tourism potential and establish tourist activity. ST strategy is improving the security services. WO strategies are increasing cooperation with the government college, arranging some promotion. WT strategies are providing education and establish a tourist village management system immediately.   Keywords : Tourism Potential, Strategy Development, TourismVillage